2016
DOI: 10.3389/fphys.2016.00190
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-Sensing Receptor and Integrins in Cellular Differentiation and Migration

Abstract: The calcium-sensing receptor (CaSR) is a widely expressed homodimeric G-protein coupled receptor structurally related to the metabotropic glutamate receptors and GPRC6A. In addition to its well characterized role in maintaining calcium homeostasis and regulating parathyroid hormone release, evidence has accumulated linking the CaSR with cellular differentiation and migration, brain development, stem cell engraftment, wound healing, and tumor growth and metastasis. Elevated expression of the CaSR in aggressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 129 publications
0
31
0
Order By: Relevance
“…In addition, it has been reported that genes downstream of G-protein coupled receptor (GPCR) signaling pathways may be the earliest response to calcium-based ceramics [ 52 ]. Indeed, calcium sensing receptor (CaSR), a receptor belonging to the GPCR family, modulates the chemotactic response of MSCs in response to extracellular calcium [ 5 , 6 , 53 ]. It has been reported that CaSO 4 induces a significant increment in Smad3 and Smad6 expression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that genes downstream of G-protein coupled receptor (GPCR) signaling pathways may be the earliest response to calcium-based ceramics [ 52 ]. Indeed, calcium sensing receptor (CaSR), a receptor belonging to the GPCR family, modulates the chemotactic response of MSCs in response to extracellular calcium [ 5 , 6 , 53 ]. It has been reported that CaSO 4 induces a significant increment in Smad3 and Smad6 expression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the CaSR prevented the mesenchymal transition and the acquisition of stem cell-like properties in the HT29 colon cancer cell line (Aggarwal et al, 2015a ) reducing the metastatic properties of the cells. Another mechanism by which CaSR might regulate adhesion and migration is the regulation of the activity of integrins, adhesion receptors that mediate cell migration (Tharmalingam and Hampson, 2016 ). Interestingly, 1,25D 3 also affects integrin signaling, as it has been shown that 1,25D 3 inhibited ionizing radiation-mediated upregulation of several integrins in keratinocytes (Muller et al, 2006 ).…”
Section: Effect Of Casr Expression and Functionality On Vitamin D Actmentioning
confidence: 99%
“…2) According to recent data, 3) cardiac fibroblasts are highly activated during diabetes, which results in dynamic balance disorder of cardiac extracellular matrix synthesis and deposition, along with the excessive deposition of collagen, thus leading to myocardial fibrosis and cardiac dysfunction. 4,5) Calcium sensing receptor (CaSR) is a member of the C family of the G protein coupling receptor superfamily and is widely expressed in both prokaryotic and eukaryotic cells. CaSR is involved in regulating the homeostasis of calcium and other metal ions, cell secretion, proliferation, differentiation, chemotaxis, apoptosis, gene expression, membrane potential, ion channel switching and aging.…”
Section: Introductionmentioning
confidence: 99%